Niobium‐Doped Titanium Dioxide: Effect of Conductivity on Metal‐Semiconductor Tribovoltaic Devices - Kaspars Mālnieks; Sabīna Kļimenko; Peter C. Sherrell; Anatolijs Šarakovskis; Raivis Eglītis; Krišjānis Šmits; Artis Linarts; Andris Šutka (Advanced Materials Interfaces)
Abstract Tribovoltaic devices have emerged as promising technologies for converting mechanical motion to electricity via surface charge generation. To maximize the electromechanical conversion of tribovoltaic devices, conventional literature has focussed on engineering a large difference in work functions between the contact materials. However, recent reports suggest that other factors beyond work function, such as temperature, play a key role in electromechanical conversion. Herein, TiO2 (a cheap, abundant oxide material) is doped with Nb5+, resulting in an improved tribovoltaic performance up to 65 times. This is attributed to an enhancement in the TiO2 film conductivity arising from Nb5+ doping. Further, it is shown that this improvement holds over cm2 scale testing. This work demonstrates the importance of considering a range of factors, particularly conductivity, when designing tribovoltaic devices and may be adopted broadly for optimal electromechanical conversion.